An Analysis of the Accusative Case Use of Learners of Turkish as a Foreign Language - Nalan KIZILTAN; Işıl ATLI (Mehmet KURUDAYIOĞLU, 2018)
Error analysis is the process of identifying, categorizing and analysing students' errors. Despite its limitations, it helps us gain a better understanding of the learning process in general and spot problematic structures for language learners. The aim of this study is to analyse the accusative case use of learners of Turkish as a second language. For that purpose, a mini-corpus was created based on 40 writing samples randomly selected from the texts produced by B2 and C1 level students at OMU Türkçe for their midterm and final exams during the previous academic years. In the examination of the mini-corpus, which includes 7177 tokens and 2991 types, the researchers initially identified all end of the word occurrences of the morpheme -i and its allomorphs. The correct and incorrect uses of the Turkish accusative case marking and the cases of omission were manually tagged by the researchers. All the erroneous uses have been classified under four headings: substitution, omission, addition and other. The findings of this study show that of 201 attempts to use the Turkish accusative case, 76 were erroneous. Besides, 62 instances of omission were manually tagged by the researchers. Of all the errors, substitution constituted 25,66%, addition 23,68 % , omission 40,79% and other errors 9,87%. The results mark the accusative case as a complex structure for learners and omission as the error category with the highest frequency. The study highlights the importance of teaching C-Selection rules with verbs.